Integrating Islamic Values Through Religious Extracurricular Activities to Strengthen Students’ Religiosity - sahrian sahrian; Muhammad Primadya; Inestia Pariza; Ahmad Jamin; Oki Mitra (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the integration of Islamic values through religious extracurricular activities in strengthening students’ religiosity at SMP Negeri 33 Mukomuko. The study focuses on the planning, implementation, and impacts of duha prayer, congregational zuhr prayer, BTQ, muhadharah, and tahfiz programs on students’ religious character. Methodology: This study employed a qualitative descriptive approach conducted at SMP Negeri 33 Mukomuko. Data were collected through in-depth interviews, participatory observation, and documentation involving 12 purposively selected informants consisting of the principal, Islamic Education teachers, homeroom teachers, school committee members, parents, and students. Data analysis used the Miles, Huberman, and Saldana interactive model with source and method triangulation. Main Findings: The findings reveal that the extracurricular religious programs were systematically planned through collaborative coordination among school stakeholders and consistently implemented using habituation and role-modeling approaches. The integration of religious activities significantly strengthened students’ religiosity across ideological, ritualistic, intellectual, experiential, and moral dimensions. Students demonstrated improvements in worship discipline, Qur’anic literacy, self-confidence, politeness, and religious awareness. Novelty/Originality of this study: This study offers an integrative analysis of multiple religious extracurricular activities within a public junior high school ecosystem. Unlike previous studies that focused on single programs, this research demonstrates the synergistic effects of combined religious activities in developing students’ religious character holistically through institutionalized habituation and teacher exemplification.